Extensions of P-property, R0-property and Semidefnite Linear Complementarity Problems - SIVAKUMAR, K.C. (Yugoslav Journal of Operations Research; Vol 27 No 2 (2017), 2017)
In this manuscript, we present some new results for the semidenite linear complementarity problem, in the context of three notions for linear transformations, viz., pseudo w-P property, pseudo-Jordan w-P property, and pseudo-SSM property. Interconnections with the P#-property (proposed recently in the literature) is presented. We also study the R#-property of a linear transformation, extending the rather well-known notion of an R0-matrix. In particular, results are presented for the Lyapunov, the Stein and the multiplicative transformations.